Manual of romance languages in the media - Bedijs, Kristina 1982-; Maaß, Christiane 1971- (Manuals of romance linguistics, 2017)
This manual provides an extensive overview of the importance and use of Romance languages in the media, both in a diachronic and synchronic perspective. Its chapters discuss language in television and the new media, the language of advertising, or special cases such as translation platforms or subtitling. Separate chapters are dedicated to minority languages and smaller varieties such as Galician and Picard, and to methodological approaches such as linguistic discourse analysis and writing process research